CURRENT PROBLEMS OF PROVISION OF PSYCHOLOGICAL ASSISTANCE TO THE FAMILIES OF SOLDIERS OF THE NATIONAL GUARD OF UKRAINE AND DIRECTIONS OF THEIR SOLUTION - Bielai, Serhii; Kernickiy, Oleksandr; Zubatenko, Taras (Honor and Law, 2022)
The article considers theoretical and practical aspects of the organization and provision of psychological assistance to the families of servicemen of Ukraine. The normative-legal base of Ukraine concerning psychological help and rehabilitation of servicemen of Ukraine, medical and social programs which are called to be realized in the regions of Ukraine is analyzed. The essence, main principles, international experience, features of psychological assistance to the families of servicemen are considered. The modern problems of providing psychological assistance to the families of servicemen of the National Guard of Ukraine are analyzed and the main directions and proposals for improving the provision of psychological assistance to such families in Ukraine are developed. When working with the families of combatants, family psychotherapy identifies two main aspects: working with them as one of the most important and significant factors in psychorehabilitation and psychological assistance to combatants who have returned from the war; providing direct psychological assistance to family members of servicemen. The results of the study showed that the successful socio-psychological rehabilitation of veterans has positive correlations with factors of family well-being, and changes in family relationships can play a key role in the implementation of psychological assistance to veterans. To design the main directions for improving work with families, the extensive structure of governmental and non-governmental organizations and institutions, volunteer and research centers, support groups for servicemen, veterans and their families, which currently operate in the United States, was analyzed. Based on this and the realities of solving the problem in Ukraine, the main directions and proposals for the organization of psychological assistance to the families of servicemen of the National Guard of Ukraine are formulated. Further work is planned to substantiate the system of providing psychological assistance to the families of servicemen of the National Guard of Ukraine.